Pećina Čelinjak (In situ, 2024)
Trial excavations of Čelinjak cave on Dugi otok continued in 2022 within the EpiC project of the Croatian Science Foundation (IP-2019-04-6115). The cave is located on the eastern side of the hill of the same name at an altitude of 111 meters above sea level, and already at first glance it reveals its archaeological potential. New research confirmed the results from the first campaign.
Keywords: Dugi otok; cave; Čelinjak; Late Antiquity; Bronze Age